ANALISIS SIKAP DAN NORMA SUBYEKTIF KELOMPOK TANI TERHADAP APLIKASI E-RDKK PUPUK BERSUBSIDI DI WKPP DESA KUALA DUA KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA - Hery Medianto Kurniawan; Sri Widarti; Fitriana Aini (Jurnal Ekonomi STIEP, 2021)
This study aims to determine the subjective attitudes and norms of farmer groups towards the application of subsidized fertilizer e-RDKK in WKPP Kuala Dua Village, Sungai Raya District, Kubu Raya Regency. This is important because it will show how big the subjective attitudes and norms of the farmer groups towards the eRDKK application are, and good subjective attitudes and norms will reflect how strong the desire of farmers or farmer groups to submit a proposal for the allocation of subsidized fertilizer needs through the e-RDKK application. This is important so that farmers' subsidized fertilizer needs can be met, so that good farming achievement and productivity can be achieved, especially for farmers and farmer groups in WKBPP Kuala Dua Village, Sungai Raya District, Kubu Raya Regency. From the results of the research, it shows that the attitude value based on the results of research analysis of 26.6112 is in the good category because it is in the range of negative values of 31.71379 and positive 31.71379, so that the attitude of farmer groups towards the application of e-RDKK in WKPP Kuala Dua Village, Sungai Raya District is good. There is a good influence of subjective attitudes and norms on the behavior of farmer groups in WKPP Kuala Dua Village on the eRDKK application. That subjective attitudes and norms have a positive effect on the behavior of farmer groups in WKPP Kuala Dua Village, Sungai Raya District, Kubu Raya Regency towards the e-RDKK application.